2009
DOI: 10.4103/0256-4947.51800
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated peritoneal Schistosoma japonicum : a case report and review of the pathological manifestations of the helminth

Abstract: Schistosomiasis (also known as bilharzia, bilharziasis, bilharziosis or snail fever) is a human disease syndrome caused by infection from one of several species of parasitic trematodes of the genus Schistosoma. The three main species infecting humans are S haematobium, S japonicum, and S mansoni. S japonicum is most common in the fareast, mostly in China and the Philippines. We present an unusual case of S japonicum in a 32-year-old Filipino woman who had schistosomal ova studding the peritoneal cavity and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Histopathological examination confirmed the diagnosis of iliac bilharzioma. A case of a Filipino woman with upper genital schistosomiasis mimicking an ovarian tumor has been previously reported by Al-Waheeb et al (2009). Although bilharzioma has been previously reported in several sites such as the kidneys (n = 2) (Amhajji et al, 2003;Diallo et al, 2011), ureters (n = 1) (Fischel, 1973), urinary bladder (n = 15) (Pieron et al, 1983;Fievet et al, 1985), epididymis (n = 1) (Fievet et al, 1985), verumontanum causing azoospermia (n = 1) (Fourcade et al, 1977), lung (n = 3) (Thompson et al, 1979;Besson et al, 1982;Rakotovao et al, 2005), small intestine (n = 1) (Ali et al, 2003), rectosigmoid (n = 3) (Elmasalme et al, 1997;Digray, 1998;Vaid et al, 2011), gall bladder (n = 1) (Ibrahim et al, 1977), and the epidural space (n = 2) (Ruberti and Saio, 1999;Maia et al, 2007), no cases of mesenteric bilharzioma have been reported.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Histopathological examination confirmed the diagnosis of iliac bilharzioma. A case of a Filipino woman with upper genital schistosomiasis mimicking an ovarian tumor has been previously reported by Al-Waheeb et al (2009). Although bilharzioma has been previously reported in several sites such as the kidneys (n = 2) (Amhajji et al, 2003;Diallo et al, 2011), ureters (n = 1) (Fischel, 1973), urinary bladder (n = 15) (Pieron et al, 1983;Fievet et al, 1985), epididymis (n = 1) (Fievet et al, 1985), verumontanum causing azoospermia (n = 1) (Fourcade et al, 1977), lung (n = 3) (Thompson et al, 1979;Besson et al, 1982;Rakotovao et al, 2005), small intestine (n = 1) (Ali et al, 2003), rectosigmoid (n = 3) (Elmasalme et al, 1997;Digray, 1998;Vaid et al, 2011), gall bladder (n = 1) (Ibrahim et al, 1977), and the epidural space (n = 2) (Ruberti and Saio, 1999;Maia et al, 2007), no cases of mesenteric bilharzioma have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Although bilharzial salpingitis has been described in previous case reports (Ekoukou et al, 1995;Schroers et al, 1995;Schanz et al, 2010), this is the first report, to our knowledge, of a case of disseminated peritoneal S. hematobium. Disseminated peritoneal Schistosoma japonicum, but without associated gynecological manifestations, has been reported by Al-Waheeb et al (2009).…”
Section: Discussionmentioning
confidence: 98%
“…Both cases led to rupture of the appendix and subsequent abscess formation but through different mechanisms. 9 The gold standard for the diagnosis of schistosomiasis is the detection of parasite ova in fecal specimens. We performed direct microscopy on three separate stool samples to look for evidence of adult worm activity, but all yielded negative for parasites or ova.…”
Section: Discussionmentioning
confidence: 99%
“…periappendiceal abscess formation. 8,9 We present an unusual case of appendiceal Schistosomiasis wherein the patient had a ruptured appendix with localized periappendiceal abscess formation.…”
Section: Introductionmentioning
confidence: 99%
“…Most human schistosomiasis is caused by Schistosoma haematobium, Schistosoma mansoni, or Schistosoma japonica, with most abdominal infections from the latter. 1 Infection is marked clinically by abdominal pain, fever, diarrhea, and cough and may result in portal or pulmonary hypertension. Abdominal infection and presentation from Schistosomiasis occurs in up to 15 per cent of infections.…”
Section: Schistosomiasis: An Unusual Cause Of Abdominal Painmentioning
confidence: 99%